Radial artery anomaly and its influence on transradial coronary procedural outcome. Issue 5 (31st October 2008) - Lo, T S; Nolan, J; Fountzopoulos, E; Behan, M; Butler, R; Hetherington, S L; Vijayalakshmi, K; Rajagopal, R; Fraser, D; Zaman, A; Hildick-Smith, D
Abstract : Background: The transradial approach for percutaneous coronary procedures has the advantage of reduced access site complications but is associated with specific technical challenges in comparison with the transfemoral approach. Transradial procedure failures can sometimes be due to variation in radial artery anatomy. However, data describing such variations are limited. Objective: To evaluate the incidence and impact of radial artery anomalies in patients undergoing transradial coronary procedures. Methods: Retrograde radial arteriography was performed in all patients presenting for a first-time radial procedure. Patient characteristics, radial artery anatomy and procedural outcome were assessed. Results: 1540 consecutive patients were studied, 70.6% male, mean (SD) age 63.6 (11.1) years. The overall incidence of radial artery anomaly was 13.8% (n = 212). 108 (7.0%) patients had a high-bifurcating radial origin, 35 (2.3%) had a full radial loop, 30 (2.0%) had extreme radial artery tortuosity and 39 (2.5%) had miscellaneous anomalies such as radial atherosclerosis and accessory branches. Overall transradial procedural success was 96.8%. Procedural failure was more common in patients with anomalous anatomy than in patients with normal anatomy (14.2% vs 0.9%, p<0.001). Procedural failure in patients with high radial bifurcation, radial loop, severe radial tortuosity and other anomalies was 4.6%, 37.1%, 23.3% and 12.9%, respectively. 15 (1%) vascular complications occurred, all of which were treated conservatively without ischaemic sequelae. Conclusion: Anomalous radial artery anatomy is relatively common and is a significant cause of procedural failure. Within each specific anomalous pattern there is a differential procedural failure rate. This has implications for clinical practice and suggests a need for imaging of the radial artery after sheath insertion.